The effect of self-efficacy on Internet usage in the organization - Ramayah, T.; Zainuddin, Yuserrie; Fok, Chee Youn (Universiti Utara Malaysia, 2003)
The rapid growth of Internet usage in organizations has become a common phenomenon in today's business world. The boom of Internet usage in organizations as a new means of performing common tasks such as communicating, finding information, disseminating information and doing marketing research, can be attributed to the benefits brought about by the Internet technology and its wide usage. In order to understand what drives an individual to use the Internet in the organizations, this study examines the impact of self-efficacy of an individual on Internet use. Self-efficacy is the belief in one's capabilities of using Internet in accomplishing specific tasks such as sending emails, searching product information and checking stock quotes. This study uses the extended technology acceptance model (TAM) proposed by Venkatesh (1999) that explicitly incorporates self-efficacy and its determinants (experience and organizational support) as factors that affect perceived ease of use, perceived usefulness and the use of Internet. A total of 104 usable responses were received from the questionnaires distributed to those who work in the organizations that provide employees with Internet access. The findings indicate that perceived usefulness has direct effect on Internet usage. Computer experience and organizational support have direct impact on self- efficacy and Internet usage. Organizational support has direct impact on perceived usefulness. Self- efficacy has direct impact on perceived usefulness and perceived ease of use of Internet usage, demonstrating its importance in the decision to use Internet and it has indirect effect on Internet usage. Perceived usefulness was found to partially mediate the relationship between computer experience and organizational support with Internet usage. It is also interesting to note that ease of use was not significant in determining Internet usage whereas perceived usefulness was, thus indicating the utility is much more important than ease of use. The implications of these findings and the limitations of this study are further discussed for the benefit of researchers and practitioners.